Uncertainty, Entrepreneurship, and Sharecropping in India - Rao, C. H. Hanumantha (Journal of Political Economy, 1971)
This study attempts to explain the coexistence of different farm lease arrangements in terms of the varying significance of entrepreneurial functions. In India, crop-sharing arrangements are common in areas of relative economic certainty with very little scope for decision making, for example, for product and factor substitution, and where the entrepreneurial profit is low. Fixed-cash rents are common in situations of high uncertainty where the scope for decision making is significant or where the crops are highly profitable. Efficiency considerations predominate in areas of sharecropping, favoring a smaller farm size, whereas, under high uncertainty, large size is favored for reducing risk.